Variations in Shaf Distance in Prayer; Comparative Study Between the Shafi'i School and the Maliki School - Ikbal, Muh (Universitas Islam Negeri Alauddin Makassar, 2021)
Prayer is one of the many obligatory matters imposed on Muslims. Therefore, in carrying out prayers, it should be done specifically, such as closing the shaf for the perfection of the prayer. But the problem that then arises is due to the Corona Virus Disease (Covid 19) phenomenon or event. The government's efforts to suppress the spread of Covid 19, one of which is the distance to prayer shafts. Prayers that are spaced apart certainly create new legal problems among Muslims. The purpose of this research is to find out the legal basis for shaf salat, the argumentation of fiqh principles on shaf salat changes and the views of the Syafi'I and Maliki Schools on shaf changes. The research method used is library research which is analytical and comparative in nature. Sources of data used in this study are secondary, primary and tertiary.Keywords: Prayer Shaf; Prayer; Imam of the School